Ginkgolide B ameliorates myocardial ischemia reperfusion injury in rats via inhibiting endoplasmic reticulum stress - Guo C; Zhang J; Zhang P; Si A; Zhang Z; Zhao L; Lv F; Zhao G (Dove Medical Press, 2019)
Changlei Guo, Junbiao Zhang, Peiyong Zhang, Aoyang Si, Zhenling Zhang, Liangping Zhao, Fenghua Lv, Guoan Zhao Department of Cardiology, The First Affiliated Hospital Xinxiang Medical University, Weihui 452100, Henan, China Purpose: Ginkgolide B (GB) is a terpene lactone component found in Ginkgo biloba, which has a protective role on ischemia reperfusion (I/R) injury. This study was aimed at exploring the protective mechanism of GB on the myocardial I/R. Patients and methods: Myocardial I/R model was established on Sprague Dawley rats. The levels of cardiac troponin I, cardiac troponin T, lactic dehydrogenase, and myoglobin were determined by a 200FR NEO automatic biochemical analyzer. Histological examination was performed through HE and terminal deoxynucleotidyl transferase-mediated dUTP nick end-labeling staining. The expression levels of p-PERK, p-IRE1α, ATF6, p-AKT, and mTOR were detected by Western blot. Results: The results exhibited that GB treatment suppressed the high levels of cardiac troponin I, cardiac troponin T, lactic dehydrogenase, and myoglobin and ameliorated the damaged and irregularly arranged myocardial cells induced by I/R injury significantly, indicating that GB could ameliorate myocardial I/R injury. Moreover, the high expression levels of endoplasmic reticulum (ER) stress key proteins caused by I/R injury were suppressed significantly by GB treatment, including p-PERK, p-IRE1α, and ATF6. GB treatment also decreased the number of apoptotic cells compared with I/R group. In addition, activation of ER stress by Tunicamycin treatment could counteract the protective effects of GB on I/R injury, suggesting that GB ameliorated myocardial I/R injury through inhibition of ER stress-induced apoptosis. Finally, the decreased p-AKT and p-mTOR expressions caused by I/R injury were upregulated by GB and inhibition of PI3K/AKT/mTOR pathway by LY294002 abolished the protective effects of GB on I/R injury, indicating that GB activated PI3K/AKT/mTOR pathway during I/R injury. Conclusion: GB protected against myocardial I/R injury through inhibiting ER stress-induced apoptosis via PI3K/AKT/mTOR signaling pathway. Keywords: myocardial injury, Ginkgolide B, endoplasmic reticulum stress, apoptosis PI3K/AKT/mTOR pathway